Serum levels of interleukin-6 are linked to the severity of the disease caused by Andes Virus - Angulo, Jenniffer; Martínez-Valdebenito, Constanza; Marco, Claudia; Galeno, Héctor; Villagra, Eliecer; Vera, Lilian; Lagos, Natalia; Becerra, Natalia; Mora, Judith; Bermúdez, Andrea; Díaz, Janepsy; Ferrés, Marcela; et al. (PLOS Neglected Tropical Diseases, 2017)
Andes virus (ANDV) is the etiological agent of hantavirus cardiopulmonary syndrome in Chile. In this study, we evaluated the profile of the pro-inflammatory cytokines IL-1β, IL-12p70, IL-21, TNF-α, IFN-γ, IL-10 and IL-6 in serum samples of ANDV-infected patients at the time of hospitalization. The mean levels of circulating cytokines were determined by a Bead-Based Multiplex assay coupled with Luminex detection technology, in order to compare 43 serum samples of healthy controls and 43 samples of ANDV-infected patients that had been categorized according to the severity of disease. When compared to the controls, no significant differences in IL-1β concentration were observed in ANDV-infected patients (p = 0.9672), whereas levels of IL-12p70 and IL-21 were significantly lower in infected cases (p = <0.0001). Significantly elevated levels of TNF-α, IFN-γ, IL-10, and IL-6 were detected in ANDV-infected individuals (p = <0.0001, 0.0036, <0.0001, <0.0001, respectively). Notably, IL-6 levels were significantly higher (40-fold) in the 22 patients with severe symptoms compared to the 21 individuals with mild symptoms (p = <0.0001). Using multivariate regression models, we show that IL-6 levels has a crude OR of 14.4 (CI: 3.3–63.1). In conclusion, the serum level of IL-6 is a significant predictor of the severity of the clinical outcome of ANDV-induced disease.